(untitled) (Editora Impacto Científico, 2025)
Climate change and air pollution are increasingly relevant environmental factors in the progression of Chronic Obstructive Pulmonary Disease (COPD), one of the leading causes of morbidity and mortality worldwide. Continuous exposure to pollutants such as fine particulate matter (PM2.5), nitrogen oxides, and sulfur dioxide, as well as extreme weather events such as heat waves and wildfires, aggravates respiratory symptoms, increases the frequency of exacerbations, and compromises patients’ quality of life. In addition to their direct impact on lung function, these environmental factors also influence systemic inflammatory responses, favoring the occurrence of cardiovascular and metabolic comorbidities. The scientific literature shows that periods of higher air pollution are associated with an increase in hospital admissions for COPD, especially in vulnerable populations, such as the elderly, people with low socioeconomic status, and residents of densely populated urban areas. Similarly, climate change intensifies the occurrence of extreme events that increase exposure to environmental pollutants, raising the risk of respiratory crises. In this context, it is essential to discuss mitigation and adaptation strategies, such as the implementation of public policies aimed at reducing pollutant emissions, the creation of warning systems for at-risk populations, and the strengthening of primary health care for early detection of decompensation. The incorporation of environmental monitoring technologies and the promotion of health education also stand out as essential tools for reducing the impact of these factors on the progression of COPD. It is concluded that addressing COPD cannot be restricted to pharmacological and clinical treatment alone, but must include integrated environmental, social, and collective health measures. Thus, understanding the relationship between climate, pollution, and COPD is an indispensable step in the development of more effective and sustainable public health actions capable of reducing the burden of disease and improving patients’ quality of life.